Changes in Fetal Cardiac Geometry with Gestation: Implications for Three-and Four-Dimensional Fetal Echocardiography - Espinoza, Jimmy (2007)
OBJECTIVE: Three- and 4-dimensional fetal echocardiography can be performed using novel algorithms. However, these algorithms assume that the spatial relationships among cardiac chambers and great vessels are constant throughout gestation. The objective of this study was to determine whether changes in fetal cardiac geometry occur during gestation. METHODS: A cross-sectional study was conducted by reviewing 3- and 4-dimensional volume data sets from healthy fetuses obtained between 12 and 41 weeks of gestation. Volume data sets were examined using commercially available software. Parameters measured included angles between: (1) the ductal arch and fetal thoracic aorta; (2) the ductal arch and aortic arch; and (3) the left outflow tract and main pulmonary artery, as seen in the short axis of the heart. The mean angle from the left outflow tract to the short axis was calculated. Nonparametric statistics were used for analysis. RESULTS: Eighty-five fetuses were included in the study. The angle between the ductal arch and the fetal thoracic aorta decreased with gestational age (Spearman coefficient: −0.39; P < .001). In contrast, the angle between the ductal arch and aortic arch, and the mean angle between the left outflow tract and the short axis of the heart increased with gestational age (Spearman’s coefficients: 0.45 and 0.40 respectively; P<.001). CONCLUSION: (1) Changes in fetal cardiac geometry were shown with advancing gestational age. (2) Proposed algorithms for the examination of the fetal heart with 3-dimensional ultrasonography may need to be adapted to optimize visualization of the standard planes before 26 weeks of gestation.